2021
DOI: 10.1111/ina.12918
|View full text |Cite
|
Sign up to set email alerts
|

Eczema, facial erythema, and seborrheic dermatitis symptoms among young adults in China in relation to ambient air pollution, climate, and home environment

Abstract: A questionnaire survey on dermal symptoms and home environment was performed in eight Chinese cities (40 279 participants). Data on city level temperature, precipitation, PM 10 , NO 2, and gross domestic product (GDP) per capita were collected. In total, 2.2% had eczema, 2.4% facial erythema (FE) and 2.6% seborrheic dermatitis symptoms (SD). Higher temperature was associated with eczema (OR = 1.09). Higher GDP per capita was related to less SD. Higher PM 10 was related to SD. Suburban living was protective for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 73 publications
2
5
0
Order By: Relevance
“…Moreover, our results also showed that children aged 0–6 years were at greater risk. These results were agreed by several other studies [ 11 , 21 ]. It is probably because children’s immune system is yet immature and their skin are tender to any ambient hazards, therefore they are susceptible to high temperature.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Moreover, our results also showed that children aged 0–6 years were at greater risk. These results were agreed by several other studies [ 11 , 21 ]. It is probably because children’s immune system is yet immature and their skin are tender to any ambient hazards, therefore they are susceptible to high temperature.…”
Section: Discussionsupporting
confidence: 94%
“…For disease types, high temperature has been found to increase the risk of skin immune diseases, especially atopic dermatitis and eczema, our finding was in line with some precious researches [ 9 , 11 , 21 ]. A time-series study in Lanzhou indicated that both extreme high temperature and moderate high temperature would increase the prevalence of atopic dermatitis, with RR of 1.85% (95%CI: 1.61%, 2.11%) and 1.45 (95%CI: 1.30%, 1.61%), respectively [ 11 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Many epidemiologic studies have examined exposure to air pollutants and the development or exacerbation of AD. While the majority of studies have found a positive relationship (Table 1) , some have reported null or inconclusive findings (Table 2) [81][82][83][84][85][86][87][88][89][90]. The variance of the results across studies may be attributable to varying criteria for the severity and diagnosis of AD in different countries, age of the participants, and the approach to outcome assessment.…”
Section: Population-level Effectsmentioning
confidence: 99%
“…Additionally, the tropical and humid environments, indoor dust mites facilitate to breed, and dust mites, which are often the trigger of allergic diseases such as allergic rhinitis and asthma [ 10 , 11 ]. Many studies have confirmed that exposure to PM 10 , PM 2.5 , NO 2 , CO, and O 3 , can deteriorate respiratory diseases [ 12 , 13 ]. Sanya, a famous tourist destination in China, boasts extensive forest coverage, a favorable climate, and excellent air quality, all of which can contribute to the recovery of allergic disorders such as asthma, among the elderly people.…”
Section: Introductionmentioning
confidence: 99%